Economic efficiency of venezuelan water companies (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
This article analyzes the economic efficiency of water companies through the ratio Venezuelan "Tobin's q", adapting the model to companies that operate as natural monopolies, in the water sector in the country. The research is documentary and field design, data processing of the financial statements provided by the C.A. HIDROVEN for a period of four years and ten of its centralized and decentralized subsidiaries, representing them through pictures. As most striking findings was that only five companies has soared to more than 1 in 13 of the 80 observations processed, the lack of economic benefits threaten the quality of service, business growth, investment in infrastructure and dependence on resources from the National Executive.
Keywords: economic efficiency; water companies; model; regulation